2008
DOI: 10.1016/j.cub.2008.02.078
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Sentinel Calling? Foragers Gain Increased Biomass Intake

Abstract: Many foraging animals face a fundamental tradeoff between predation and starvation. In a range of social species, this tradeoff has probably driven the evolution of sentinel behavior, where individuals adopt prominent positions to watch for predators while groupmates forage. Although there has been much debate about whether acting as a sentinel is a selfish or cooperative behavior, far less attention has focused on why sentinels often produce quiet vocalizations (hereafter known as "sentinel calls") to announc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 25 publications
3
100
1
Order By: Relevance
“…However, meerkats administered with exogenous cortisol took, on average, 12.5 s longer to resume foraging in response to alarm call playbacks. During this amount of time, meerkats may find and eat prey (mean prey catch rate: one every 2 -3 min Carlson et al, 2006) and thus, our observed increase in latency to resume foraging could result in decreased food intake (Hollén et al, 2008). Additional factors, such as distance to shelter or neighbors, as well as response of neighbors to the alarm call playbacks could also have influenced latency to resume foraging, increasing data variation and thus decreasing statistical power.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, meerkats administered with exogenous cortisol took, on average, 12.5 s longer to resume foraging in response to alarm call playbacks. During this amount of time, meerkats may find and eat prey (mean prey catch rate: one every 2 -3 min Carlson et al, 2006) and thus, our observed increase in latency to resume foraging could result in decreased food intake (Hollén et al, 2008). Additional factors, such as distance to shelter or neighbors, as well as response of neighbors to the alarm call playbacks could also have influenced latency to resume foraging, increasing data variation and thus decreasing statistical power.…”
Section: Discussionmentioning
confidence: 89%
“…Increased vigilance can lead to decreased foraging activity and food intake. Thus, even though the effect of increased fGC concentrations on vigilance rates is small, it could result in decreased food intake and thus lead to fitness consequences (Hollén et al, 2008). Because environments and threats can be highly variable, the ability to adjust behavioral strategies and time-budgets according to environmental conditions is critical for survival (Mateo, 2007;Zanette et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Meerkats need to roam widely to find food, and they frequently change sleeping burrows in their territory (Manser and Bell 2004). Meerkats, but not Cape ground squirrels, have evolved cooperative vigilance, with sentinel duties decreasing the individuals' time spent vigilant (Manser 1999), likely increasing their foraging efficiency (as in pied babblers; Hollén et al 2008). A meerkat losing contact with the rest of the group due to taking a different escape direction than its group mates may experience severe costs, as single meerkats and small groups suffer much higher predation than larger groups (Clutton-Brock et al 1999a).…”
Section: Evolution Of Alarm Calls 407mentioning
confidence: 99%
“…A striking illustration of this is the sentinel behaviour seen in some social vertebrates, where group members suspend foraging, adopt a raised position and look out for danger [7][8][9]. Sentinel bouts within groups are tightly coordinated, with individuals typically taking turns and there rarely being more than one or two engaging in this activity at any one time [8,9]. In such situations, vigilance decisions are anything but a sealed bid.…”
mentioning
confidence: 99%
“…While it is now apparent that foraging does not necessarily prevent individuals from gathering some visual information about predators and/or conspecifics, it is likely that scanning is compromised to some extent [12]. In many social species, individuals use continuous quiet vocalizations to stay in contact with one another, both when foraging [13,14] and when being vigilant [9,15]. There is growing evidence that these 'close' calls can be used by other group members to assess the need for vigilance [16][17][18], although it remains unclear precisely how much information is directly conveyed about the caller's current behaviour.…”
mentioning
confidence: 99%